The Effect of Mobile Service Quality on Continuance Intention Mediated by Perceived Value and Customer Satisfaction Among Users of the Mytelkomsel App in Banda Aceh (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study aims to examine the effect of mobile service qualityon continuance intention in the MyTelkomsel application, with perceived value and customer satisfaction as mediating variables. Data were collected through an online questionnaire distributed to 200 respondents who are users of the MyTelkomsel application in Banda Aceh, using a non-probability sampling technique with purposive sampling method. The results of the analysis indicate that mobile service qualityhas a positive and significant direct effect on continuance intention, perceived value, and customer satisfaction. Perceived value does not have a positive and significant direct effect on continuance intention and therefore does not mediate the relationship between mobile service qualityand continuance intention. Meanwhile, customer satisfaction has a positive and significant direct effect on continuance intention and partially mediates the relationship between mobile service qualityand continuance intention.